Studi Tafsir Tematik Ayat tentang Konsep Membelanjakan Kekayaan - Wildah Nurul Islami (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2019)
The Qur'an describes the concept of spending wealth as an urgent matter to study. Spending wealth is to produce one's property for one's own needs or to give it to others who need it. The method used to understand the concept of spending wealth is a thematic interpretation of the verse. The word spend wealth `in Arabic is often called s arafa al-ma> l which means the same as anfaqa al-ma> l used as a keyword. The next step is to classify the verses based on their origin (makk?yyah-madan?yyah). From the analysis of the verses on spending the wealth, there are 5 main topics, including the order to spend the wealth, the purpose of spending the wealth is due to God, the principles of spending the wealth include the criteria for spending the wealth, time to spend the wealth, the prohibition on spending the wealth, there is a spending of wealth, in the form of zakat and sadaqah, the priority of those who spend their wealth is that God can bestow and multiply his reward.